Culture works : the political economy of culture - Maxwell, Richard, 1957- (Cultural politics (Minneapolis, Minn.) ;, 2001)
This book offers readers a number of ways to link cultural experience to political economyto become aware of the ways in which political and economic realities and decisions determine the outlines of spaces and activities in everyday life. Unsettling and provocative, Culture Works shows how particular economies and power relations work in familiar and central cultural experiences: art, beer, advertising, dance, sport, shopping, the Web, and media.